Intensity Thresholds and Maximal Lactate Steady State in Small Muscle Group Exercise - Florian Spendier; Alexander Müller; Markus Korinek; Peter Hofmann (MDPI AG, 2020)
The aim of our study is to determine the first (LTP1) and the second (LTP2) lactate turn points during an incremental bicep curl test and to verify these turn points by ventilatory turn points (VT1 and VT2) and constant-load exercise tests. Twelve subjects performed a one-arm incremental bicep curl exercise (IET) after a one repetition maximum (1RM) test to calculate the step rate for the incremental exercise (1RM/45). Workload was increased every min at a rate of 30 reps/min until maximum. To verify LTPs, VT1 and VT2 were determined from spirometric data, and 30 min constant-load tests (CL) were performed at 5% Pmax below and above turn points. Peak load in IET was 5.3 ± 0.9 kg (Lamax: 2.20 ± 0.40 mmol·L−1; HRmax: 135 ± 15 b·min−1; VO2max: 1.15 ± 0.30 L·min−1). LTP1 was detected at 1.9 ± 0.6 kg (La: 0.86 ± 0.36 mmol·L−1; HR 90 ± 13 b·min−1; VO2: 0.50 ± 0.05 L·min−1) and LTP2 at 3.8 ± 0.7 kg (La: 1.38 ± 0.37 mmol·L−1; 106 ± 10 b·min−1; VO2: 0.62 ± 0.11 L·min−1). Constant-load tests showed a lactate steady-state in all tests except above LTP2, with early termination after 16.5 ± 9.1 min. LTP1 and LTP2 could be determined in IET, which were not significantly different from VT1/VT2. Constant-load exercise validated the three-phase concept, and a steady-state was found at resting values below VT1 and in all other tests except above LTP2. It is suggested that the three-phase model is also applicable to small muscle group exercise.